Incidence, risk factors, and outcomes of the transition of HIPEC-induced acute kidney injury to acute kidney disease: a retrospective study - Yunwei Lu; Ziyan Xiao; Xiujuan Zhao; Yingjiang Ye; Shu Li; Fuzheng Guo; Haiyan Xue; Fengxue Zhu (Renal Failure)
Background Acute kidney injury (AKI) is recognized as a common complication following cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC). Characterized by prolonged renal function impairment, acute kidney disease (AKD) is associated with a higher risk of chronic kidney disease (CKD) and mortality.Methods From January 2018 to December 2021, 158 patients undergoing CRS-HIPEC were retrospectively reviewed. Patients were separated into non-AKI, AKI, and AKD cohorts. Laboratory parameters and perioperative features were gathered to evaluate risk factors for both HIPEC-induced AKI and AKD, with the 90-day prognosis of AKD patients.Results AKI developed in 21.5% of patients undergoing CRS-HIPEC, while 13.3% progressed to AKD. The multivariate analysis identified that ascites, GRAN%, estimated glomerular filtration rate (eGFR), and intraoperative (IO) hypotension duration were associated with the development of HIPEC-induced AKI. Higher uric acid, lessened eGFR, and prolonged IO hypotension duration were more predominant in patients proceeding with AKD. The AKD cohort presented a higher risk of 30 days of in-hospital mortality (14.3%) and CKD progression (42.8%).Conclusions Our study reveals a high incidence of AKI and AKI-to-AKD transition. Early identification of risk factors for HIPEC-induced AKD would assist clinicians in taking measures to mitigate the incidence.